Erratum: Meningkatkan Hasil Belajar Perwasitan Bolavoli Menggunakan Model Pembelajaran Team Games Tournament - Pnatmo Welhelmin Masi; Magdalena Rambu Pisu Wasak (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.818 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.